Cover Picture: A Novel Biomimetic Hydrogen Peroxide Biosensor Based on Pt Flowers‐decorated Fe3O4/Graphene Nanocomposite (Electroanalysis 6/2017). Issue 6 (June 2017) - Zhao, Xueling; Li, Zhanhong; Chen, Cheng; Wu, Yihua; Zhu, Zhigang; Zhao, Hongli; Lan, Minbo
Abstract : The cover picture shows a sensitive and selective amperometric H2 O2 biosensor which was obtained by utilizing the electrodeposition of Pt flowers on iron oxide‐reduced graphene oxide (Fe3 O4 /rGO) nanocomposite modified glassy carbon electrode (GCE). Details are discussed in the article by Xueling Zhao et al. on page1518 .